Perfíl tiroideo en mujeres embarazadas que cursan el primer trimestre de gestación y mujeres no embarazadas en edad fértil, que acuden al Hospital Julius Doepfner de Zamora. - Sarango Jima, Magali Patricia (2013)
The thyroid isa glandthat controlsimportant functionsof the body,disordersdue toits malfunctioncan affectnearly every organof the body andbe harmfulto health.These disorderssuch as hypothyroidism, hyperthyroidism, thyroiditis, among others, are presentedby increasedordecreased levelsof thyroid hormonesin the bloodand represent30-40% ofthe population,such thatmay occur instagereproductivecausingmenstrual disturbances,galactorrhea, infertility and abortiontorepeat, among others. These possibilitiesincrease with agebetween 25 and65 years, female gender, familymedical history, iodinedeficiency, autoimmune diseases, among others.Existingthreeriskgroups or populationssuch asschool children,womenof childbearing ageand pregnant women.We thereforeconducted adescriptive,cross-sectional, whichwas determinedbyELISAenzyme immunoassaymethod(MicroElisa), the thyroidprofile(TSH, TT3, T4t) in pregnant women enrolled in thefirst trimester of pregnancyandwomenpregnant womenof childbearing age,who come to thehospitalDoepfnerZamoraJuliusandhimselfdrew comparisonsregardingthyroidhormone concentrationsin the two groups. After theinvestigation it was determinedthatof the 40non-pregnant women, 17.5% patients hadincreased levels ofTSH, whereas in 82.5% TSHlevelsremained normalandtoassess levels ofT3tandT4tin 100%isfoundnormal. In the groupof pregnant women100% had TSHlevelswithin the normal range, while 2.5% presented andT4tT3tlevelsincreased inthe first month ofpregnancy.Based on thesedatait is evident thatthenon-pregnantgroups are those withalterations interms of values​​of thyroid hormones.The results weredisseminatedto the medical staffandpatients toknow theimportance of studying thethyroid profileinfertilewomen. Keywords:Thyroid Profile, thyrotropin(TSH), serum total triiodothyronine(T3t) andtotal thyroxine(T4t)